AKT inhibition interferes with the expression of immune checkpoint proteins and increases NK-induced killing of HL60-AML cells - Sofia Mônaco Gama; Vanessa Araújo Varela; Natalia Mazini Ribeiro; Bruna Bizzarro; Camila Hernandes; Thiago Pinheiro Arrais Aloia; Mariane Tami Amano; Welbert Oliveira Pereira (Einstein (São Paulo), 2023)
ABSTRACT Objective To determine the role of the AKT pathway in the regulating of natural Killer-induced apoptosis of acute myeloid leukemia cells and to characterize the associated molecular mechanisms. Methods BALB/c nude mice were injected with HL60 cells to induce a xenogenic model of subcutaneous leukemic tumors. Mice were treated with perifosine, and their spleens were analyzed using biometry, histopathology, and immunohistochemistry. Gene expression analysis in leukemia cells was performed by real-time PCR. Protein analysis of leukemia and natural Killer cells was performed by flow cytometry. AKT inhibition in HL60 cells, followed by co-culture with natural Killer cells was performed to assess cytotoxicity. Apoptosis rate was quantified using flow cytometry. Results Perifosine treatment caused a reduction in leukemic infiltration in the spleens of BALB/c nude mice. In vitro , AKT inhibition reduced HL60 resistance to natural Killer-induced apoptosis. AKT inhibition suppressed the immune checkpoint proteins PD-L1, galectin-9, and CD122 in HL60 cells, but did not change the expression of their co-receptors PD1, Tim3, and CD96 on the natural Killer cell surface. In addition, the death receptors DR4, TNFR1, and FAS were overexpressed by AKT inhibition, thus increasing the susceptibility of HL60 cells to the extrinsic pathway of apoptosis. Conclusion The AKT pathway is involved in resistance to natural Killer-induced apoptosis in HL60 cells by regulating the expression of immune suppressor receptors. These findings highlight the importance of AKT in contributing to immune evasion mechanisms in acute myeloid leukemia and suggests the potential of AKT inhibition as an adjunct to immunotherapy.